SIMULASI ALIRAN KONVEKSI FLUIDA DI DAERAH RESERVOIR PANAS BUMI - Alamta Singarimbun; Famelia Nurlela (Jurnal FisTa : Fisika dan Terapannya, 2020)
The potential of geothermal energy can be determined by the potential classification based on performed simulation. The simulation results show the quality of geothermal energy utilization can be optimized. Under natural conditions, a geothermal system consists of a heat source, the bedrock layer, reservoir layer, and caprock layers. The process of conduction heat transfer occurs when a heat source to transfer heat to the bedrock and bedrock is heat transfer by convection to the reservoir. The heat transfer process makes the temperature at any depth is different and will change with time. Numerical simulation and modeling of two-dimensional sebara done to simulate the fluid temperature in the geothermal reservoir which satisfies equations of fluid flow in a porous medium for single-phase flow (Darcy's law). The observed parameters are the temperature distribution, pressure, and direction of fluid flow in a reservoir. Didiskritisasi mathematical equations using finite difference or difference-up. The computational process is done by using Matlab software